PERAN WORK LIFE BALANCE DAN STRES KERJA DALAM MENINGKATKAN KESEHATAN MENTAL KARYAWAN PERUSAHAAN START-UP - Dodi Setiawan Riatmaja; Dinda Sukmaningrum; Ammar Surya Ramadhan (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2026)
The growth of start-up companies in Indonesia drives an increased demand for digital workforce operating in dynamic, flexible, and high-pressure environments. This condition heightens the risk of mental health disturbances due to work-life imbalance and prolonged stress. This research aims to analyze the influence of Work Life Balance and Work Stress on the Mental Health of start-up company employees. The research method employed a quantitative approach with 250 respondents selected through purposive sampling. Data were collected via a Likert scale questionnaire (1–5) and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) through SmartPLS 4.0 software. The research findings indicate that Work Life Balance has a significant positive effect on Mental Health, while Work Stress has a significant negative effect on Mental Health. Furthermore, Work Life Balance was also proven to significantly reduce the level of Work Stress. The R² value shows that Work Life Balance and Work Stress explain 57.7% of the variance in Mental Health, while Work Life Balance explains 51.2% of the variance in Work Stress. These findings confirm that work-life balance is a crucial protective factor for the psychological stability of start-up employees, whereas work stress is a primary risk factor that diminishes mental health. This research offers important implications for start-up management to enhance work-life balance policies, improve organizational support systems, and create sustainable work environments to maintain employee mental health in the long term.